2020
DOI: 10.3390/plants9030310
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Growth, Cadmium Accumulation and Tolerance of Three Chickpea (Cicer arietinum L.) Cultivars

Abstract: Trace metals (TM) contamination is a severe problem in the environment and produced an adverse effect on the productivity of crops. Cadmium (Cd) is a TM ranked seven among the top 20 pollutants due to its high toxicity and solubility in water, taken up by the plants and affects their growth and metabolism. In this study, we evaluated the growth, Cd accumulation and tolerance capacities of three chickpea (Cicer arietinum L.) cultivars (NC234 (NC2), ICCV89310 (IC8) and ICCV89323-B (IC8-B)), subjected to two Cd c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 57 publications
4
27
0
Order By: Relevance
“…These growth-inhibiting effects of Cd on pigeon pea may be attributed to the significant decrease in photosynthetic activities, nutrient deficiency, and excessive ROS production (Tables 1 and 2; Figure 1). Previous studies have reported similar reduced growth attributes in other plant species due to cadmium stress [14,15,52,53]. Photosynthesis is plants' life-sustaining process and is often sensitive to metal stresses.…”
Section: Discussionmentioning
confidence: 66%
“…These growth-inhibiting effects of Cd on pigeon pea may be attributed to the significant decrease in photosynthetic activities, nutrient deficiency, and excessive ROS production (Tables 1 and 2; Figure 1). Previous studies have reported similar reduced growth attributes in other plant species due to cadmium stress [14,15,52,53]. Photosynthesis is plants' life-sustaining process and is often sensitive to metal stresses.…”
Section: Discussionmentioning
confidence: 66%
“…Exposure of plants to Zn has been reported to affect root and shoot growth parameters, including root and shoot lengths, fresh weights and dry weights which are all considered very sensitive parameters used as indicators to the response of plants towards Zn resistance and toxicity. The degree of these effects are dependent on soil Zn concentrations, plant species, genotype and also plant tissue (Kumar et al, 2012, Shakir et al, 2020. El-Dahshouri et al 2017worked on the effect of foliar application of Zn on the sandy soil-cultivated wheat cultivar Sakha 94, which is studied in this work, and the wheat cultivar Gemmyza 9 from the same line of the other cultivar in this work, Gemmyza 10.…”
Section: Resultsmentioning
confidence: 86%
“…Zinc treatment in this work reduced the roots fresh weights of cultivar Sakha 94 by 45% in comparison with only 23% reduction in the fresh weights of the shoots of the same cultivar. Roots are the first plant organs that are subjected to soil pollutants, so they are more sensitive to metal toxicity than shoots (DalCorso et al, 2019, Huang et al, 2020, Shakir et al, 2020. The inhibition of shoots and roots elongation resulted from heavy metals treatment may be due to their influence on cell division (Hargemeyer, Breckle, 1996) or cell wall elasticity and metabolic activities (Naseer et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…There were three replicates for determining the Cd concentration of each plant. The accumulation of Cd in plant parts and translocation factor (TF) of Cd from roots to shoots were evaluated as follows (Ullah et al 2020):…”
Section: Plant Analysismentioning
confidence: 99%